Connecting Fantasy Worlds and Nostalgia: Miyazaki Gorō’s Animation Movies - M. M. Grajdian (Russian Japanology Review)
In the particular context of post-Cold War Japanese animation, the name of Miyazaki Gorō 宮崎 吾朗 (born 1967) is mostly related to the name of his illustrious father, Miyazaki Hayao 宮崎 駿 (born 1942). Professionally speaking, Miyazaki Gorō is a landscaper (construction consultant in the planning and designing of parks and gardens) as well as an animation director of two animation movies and one TV animation series. This paper focuses on the two animation movies released by Studio Ghibli under Miyazaki Gorō’s direction: Tales from the Earthsea (ゲド戦記 Gedo senki, 2006) and From Up On Poppy Hill (コクリコ坂から Kokuriko-zaka kara, 2011). Miyazaki Gorō’s two animation movies are described and analyzed, both as ideological manifestos continuing and, from a certain point onward, transcending what might be called the “Ghibli paradigm” and as aesthetical masterworks combining the “Ghibli paradigm” with fresh visions of employing animation as a medium, exploring, absorbing and integrating influences from beyond geographical boundaries and striving to break the “Japanese” limitations of the artistic language utilized in his approach to animated expressive modes.